Long-term oral creatine supplementation does not impair renal function in healthy athletes - Poortmans, J. R.; Francaux, M. (Medicine & Science in Sports & Exercise, 1999)
Neither short-term, medium-term, nor long-term oral creatine supplements induce detrimental effects on the kidney of healthy individuals.